MONEY SLAVERY - Mashkov V.V. (European Scientific Journal, ESJ, 2014)
Money basically performs auxiliary role in promoting good development and the manufacture and selling of goods and services. Thus, money should not be substituted for goods. Money is a means used for the measurement of capital. On the other hand, capital is the real resources that producers use in order to make the goods that we all consume: things like factories, machine tools, trucks, and roads. Money on the other hand is non-specific; it can be used to buy anything that is available in the marketplace, including capital goods. This is what leads to the common practice of referring to money as capital. When money becomes goods, too much money will be in circulation, and when this occurs, the overflow of the money often results to global economic crisis and to economic explosion. The Cult of money creates in the society, special status superiority on money-racial criterion and this violates the right to Liberty and equality.